KONSEP JIHAD DALAM KUTUB AT-TIS'AH (STUDI MAUDU'I) - Rohmansyah, Rohmansyah (Al-MAJAALIS, 2016)
Based on the results of the study, there are about 146 hadith; between 54 jihÃ¢d concept and 92 suport jihÃ¢d hadith that have been collected from Kutub at-Tisâ??ah that result in the concept of jihÃ¢d, which is the definition of the jihÃ¢d, the kinds of the jihÃ¢d, the procedure of the jihÃ¢d, and the philosophy of the jihÃ¢d. The jihÃ¢d means mobilizing all of the capabilities in terms of spirits and materials and avoiding blamable conducts in order to be close to Allah SWT. Additionally, the jihÃ¢d also means learning religious knowledge and teaching others the knowledge. The kinds of the jihÃ¢d include the jihÃ¢d against polytheists (musyrik), the jihÃ¢d against desires, and the jihÃ¢d against tyrant. The procedure of the jihÃ¢d includes good intention (niat), parental permission, organized collectively, and under the command of a leader. The philosophy of the jihÃ¢d is to spread Islamic knowledge, to deny hostility and evil, to protect and to defend self and possessions, to express truth and justice, to socialize good and noble conduct and to materialize Islamic values in social, national and state lives.